Including Legumes in Wheat-Bermudagrass Pastures - L. W. Lomas; J. L. Moyer (Kansas Agricultural Experiment Station Research Reports, 2019)
Use of legumes in wheat-bermudagrass pastures did not affect summer cow gains in 2018. Forage availability was greater (P<0.05) where nitrogen (N) alone was used than where crimson clover and ladino clover were used in the Legume system. Estimated forage crude protein (CP) was similar (P>0.05) for the Legume and Nitrogen systems.
Keywords: bermudagrass; cows; grazing; crimson clover; ladino clover; wheat; nitrogen